Landscape-ecological approach to the formation of urban space - Chernysh Наталья (Рroblems of engineering and professional education, 2023)
The need for a landscape-ecological solution is based on the creation of urban planning. Among them, the urban landscape is considered as a highly complex system that has a hierarchical level and incorporates basic categories and structural elements. The functioning of such a system is carried out on the basis of the environment of reference environmental norms.